KONSTRUKSI PEMBELAJARAN ANDRAGOGI DALAM MENTORING BEASISWA ONLINE: STUDI KASUS ADAPTASI PRINSIP PEMBELAJARAN ORANG DEWASA MENGGUNAKAN INFRASTRUKTUR DIGITAL: KONSTRUKSI PEMBELAJARAN ANDRAGOGI DALAM MENTORING BEASISWA ONLINE: STUDI KASUS ADAPTASI PRINSIP PEMBELAJARAN ORANG DEWASA MENGGUNAKAN INFRASTRUKTUR DIGITAL - Nurhadi, Harun; Putra, Ari; Dwi palenti, Citra; Junaidi, Febi (Jurnal Obor Penmas: Pendidikan Luar Sekolah, 2026)
This study describes the construction of andragogy learning in an online scholarshipmentoring class at BimacitaGlobal, South Bengkulu. This study involved six informantsconsisting of managers, mentors, and participants of the Master's and Doctoralscholarship programs. The researchers used a descriptive qualitative approach with datacollection techniques through in-depth interviews, participant observation, anddocumentation. The researchers analyzed the data using triangulation of sources andmethods. The results show that this online mentoring program applies the principles of,The results of the study indicate that this online mentoring program consistently appliesandragogy principles in three stages: planning, implementation, and evaluation. Thisprogram integrates synchronous learning via Zoom, asynchronous learning via GoogleClassroom, and ongoing communication via WhatsApp. The findings of this study lie inthree aspects: (1) Researchers found a unique andragogy adaptation model in the contextof limited digital infrastructure, specifically a hybrid flexibility strategy that combinessynchronous-asynchronous learning with intensive personal mentoring; (2) Researchersidentified a unique social construction of learning through mentor-participant interactionsin virtual spaces, which resulted in active participation patterns based on digital learningcommunities; and (3) Researchers develop an online adult learning evaluation frameworkthat integrates the dimensions of technological readiness, intrinsic motivation, andachievement of scholarship competencies. The theoretical contribution of this researchenriches the understanding of the implementation of andragogy in digital learning foradults, while its practical contribution provides a learning model that can be adapted bynon-formal educational institutions in areas with similar limitations.